Cytogenotoxicity biomarkers in fat snook Centropomus parallelus from Cananéia and São Vicente estuaries, SP, Brazil - Kirschbaum, Aline A.; Seriani, Robson; Pereira, Camilo D.S.; Assunção, Andrea; de Souza Abessa, Denis M. [UNESP]; Rotundo, Matheus M.; Ranzani-Paiva, Maria J.T. (FapUNIFESP (SciELO), 2009)
The aquatic environment receives many contaminants that can induce damages at the molecular, biochemical, cellular and physiological levels. Centropomus parallelus, an important food resource for local populations, is a predator fish that feeds on small fishes and benthic invertebrates, thus being vulnerable to the bioconcentration and biomagnification processes. This study aimed to evaluate cytogenotoxic responses in erythrocytes from C. parallelus juveniles collected in the Cananéia and São Vicente estuaries, both in winter and in summer. After anesthesia, blood samples were collected by caudal puncture. Blood smears were prepared on glass slides and stained with May-Grünwald-Giemsa dye. Two thousand cells were analyzed per slide (1000x), and nuclear abnormalities (NA) and micronuclei (MN) were scored. The São Vicente sample showed MN and NA frequencies (%/1000 cells) of 0.325 and 3.575, in winter, and of 0.125 and 2.935 in summer respectively; the Cananéia sample showed frequencies of 0.0325 and 0.03, in winter, and of 0.065 and 0.355 in summer, respectively. The rates found in São Vicente were significantly higher than those found in Cananéia, evidencing that the levels of pollution in that estuary were high enough to induce genetic damages. Copyright © 2009, Sociedade Brasileira de Genética.
Keywords: Centropomus parallelus; Cytogenotoxicity; Micronuclei; Nuclear abnormalities